The Landscape of Contemporary Architectural Practices in Indonesia - Nadizti, Fath; Hanan, Himasari (Talenta Publisher, 2025)
Indonesia's contemporary architecture has developed in response to globalisation, urbanisation, and modernisation, striking a balance between regional customs and global tendencies. This research analyses projects displayed at the Indonesian Architects Week (IAW) 2024 exhibition in order to investigate the state of contemporary architecture in Indonesia. Key architectural trends in residential, office, hospitality, commercial, government, and public areas are highlighted by the research, which groups these projects according to their function and geographic distribution. The results show that private-sector demands drive contemporary architectural practices, with Java and Bali & Nusa Tenggara having the highest concentration of projects, while Sumatra, Sulawesi, Kalimantan, and Papua & Maluku continue to be under-represented. A trend towards mixed-use architectural designs is also noted in the report, as demonstrated by buildings that combine several uses, including office-commercial, government-public, and residential-office hybrids. Despite these revelations, the study's limitations include its only dependence on exhibition data and the absence of primary research methods like stakeholder participation, field observations, or interviews. It does not, therefore, offer a completely generalisable depiction of modern architectural techniques in Indonesia. However, it provides a useful foundation for further research into the innovations, problems, and trends influencing Indonesia's built environment. To gain a more thorough grasp of how Indonesian contemporary architecture is still changing within regional, cultural, and economic contexts, future research should apply direct architectural analysis and larger datasets.